Behavioral Effects and Pharmacokinetics of Low-Dose Intravenous Alcohol in Humans. - Davidson, Dena; Camara, Paul; Swift, Robert (Alcoholism: Clinical & Experimental Research, 1997)
Alcohol has physiological effects on the human central nervous system at blood alcohol concentrations (BACs) as low as 9 mg/dl. It is unknown, however, if humans can perceive the effects of such low doses of alcohol. Furthermore, low BACs can be difficult to measure. The purpose of this experiment was to: (1) assess the ability of humans to perceive subjective effects of low BACs; (2) measure behavioral effects of low BACs on a psychomotor performance task; and (3) test the sensitivity and accuracy of the transdermal alcohol sensor (TAS) for measuring low BACs from skin. Five men and seven women were administered single-blind intravenous infusions of ethyl alcohol in 5% dextrose/water to achieve peak BACs of 0,10,20, and 40 mg/dl. Subjective intoxication scales and a computer administered continuous performance task (CPT) were used to assess alcohol effects. BACs were estimated from skin, blood, and breath. The only alcohol-induced sensation significantly increased during the alcohol infusions was anesthesia measured by the Alcohol Sensation Scale on the descending limb of the BAC curve. The subjective positive-reinforcing stimulant and mood effects of alcohol were not reported until subjects were administered the 40 mg/dl alcohol infusion. Other measures of subjective intoxication and sedation, and the CPT were unaffected by the alcohol infusions. The TAS provided a noninvasive method for estimating BACs that was comparable with estimates obtained from blood and breath, although delayed in time.